A formação continuada na interface da prática pedagógica de professores: um estudo com docentes da Educação Básica - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This research had as object of study the continuing education, at master's level, developed in the Graduate Program in Teaching of Sciences and Humanities of the Institute of Education, Agriculture and Environment, Federal University of Amazonas. Considering that this formation has become one of the bets of education for the professional development of teachers and, making sure of the constant changes that occur in the educational scenario that require professionals to invest in their own formation, the research listed as main objective to analyze the contributions of continuing education, at the master's level, for the development of pedagogical practices of basic education teachers, from state schools in the city of Humaitá/AM. The research was designed from a qualitative approach supported by phenomenology, using the narrative interview technique to give voice and turn to nine teachers with a master's degree. The interpretation of the data followed the theoretical path of Content Analysis and the theoretical and methodological contribution was based on studies by Nóvoa (1999, 2013); Marcelo García (1999, 2009); Souza (2006, 2007); Huberman (2013); Cunha (2012, 2013, 2014); Bardin (2014); Silva (2015, 2019) and others who discuss the theme in their research. In the eagerness to answer the problematic and achieve the major objective of the research, more specific objectives were defined: to identify the profile of teachers who undertook continuing education in stricto sensu post-graduation; to describe the challenges and difficulties in relation to the teachers' pedagogical practice; to analyze the implications of continuing education for pedagogical practice and for teachers' professional development. The results indicated that: i) the self-training path for teaching presented moments of approximations and singularities (financial need, family support, resilience); ii) in the path of professional performance the teachers entered without any previous practice iii) the experiences in continuing education were permeated with challenges and difficulties, and other adverse ones requiring from the teachers resilience, but of intense learning; iv) the teachers' perception about the formation they experienced was the re-significance of the pedagogical practice; v) the formative process emerged positive implications for the development of the subjects they teach and for the teachers' professional development; vi) in their voices, the formation is configured with the meaning of appropriating a permanent learning that strengthens and enhances the practice exercise and the work among peers and collectively at school. The continuing education also stimulated the perception of self, provoking in teachers changes for the construction of a new image and more active, autonomous and critical attitudes of their own practices.
Keywords: Professores - Formação; Professores de pós-graduação; CIENCIAS HUMANAS: EDUCACAO; Formação continuada; Prática pedagógica; Percepção docente; Desenvolvimento profissional docente